Upwelling shapes nitrate isotope distribution in the Seychelles–Chagos Thermocline Ridge in the Indian Ocean - Jeong, Seonghee; Hahm, Doshik; Kang, Dong-Jin; Rho, TaeKeun; Kang, Sujin; Son, Purena; Lee, Tongsup (Frontiers in Marine Science, 2025)
The Seychelles–Chagos Thermocline Ridge (SCTR) is a persistent open-ocean upwelling region, yet its nitrate-isotope dynamics remain sparsely documented. To clarify how physical transport and biological uptake shape these signals, we measured nitrate concentrations and dual-isotope ratios (δ15N, δ18O) along a meridional section in the southwestern tropical Indian Ocean. Below the upper layer, isotopic compositions primarily reflect the origin and biogeochemical history of distinct water masses, including Circumpolar Deep Water from the south and denitrification-influenced Red Sea Overflow Water from the north. In the upper 100 m, however, patterns depart from simple Rayleigh or steady-state expectations and are best explained by two-end-member mixing between newly upwelled, low-isotope nitrate and surface waters containing isotopically enriched residual nitrate from prior assimilation. The mixing imprint becomes detectable only when nitrate drawdown exceeds ∼80%, indicating that physical mixing can overprint classical assimilation signals under moderate consumption. Together, these results clarify when curved trajectories in nitrate-isotope space should appear and provide a practical basis for interpreting nitrogen cycling in upwelling systems where nutrient supply, water-mass advection, and biological uptake jointly control the observed isotope distributions.